Risk Factors for Incident Vascular Graft Infections. (4th October 2017) - Anagnostopoulos, Alexia; Ledergerber, Bruno; Kuster, Stefan P; Scherrer, Alexandra U; Näf, Bettina; Zbinden, Reinhard; Rancic, Zoran; Bettex, Dominique; Lachat, Mario; Hasse, Barbara
Abstract: Background: Due to the aging of the population, open and endovascular reconstructive vascular surgery has become increasingly common. Vascular graft infections (VGI) are serious complications with a cumulative incidence rate of 1 - 6%, leading to increased morbidity and mortality. Previously described associations with VGI include groin incision, extended procedure time, comorbid conditions, and local wound infections. We aimed to identify potentially avoidable risk factors for VGI, which are important measures for improved future infection prevention strategies. Methods: Participants of the prospective Vascular Graft Infection Cohort (VASGRA) with vascular surgery between May 2013 and April 2017 were included. Observation time was calculated from vascular surgery until confirmed VGI or last follow-up, whichever occurred first. Patient- and procedure-related variables were assessed by infection status using chi-square test, Fishers exact test or Wilcoxon rank-sum test, whichever was appropriate. Uni- and multivariable Cox proportional hazard regression models, adjusted for demographic factors, were applied to assess risk factors for developing a VGI. Results: A total of 415, predominantly male (84%) patients with a median age of 71 years contributed to 385 person years (PY) of follow-up. Thereof, 34 (8.2%) developed a VGI, amounting to an incidence rate of 8.8/100 PY [95% CI 6.3–12.4]. Open surgery (adjusted Hazard Ratio (aHR) 2.2 [95% CI 1.02–4.78]) and extended procedure time (aHR 1.1 [1.02–1.19] (per hour)) were found to be risk factors for VGI (Figure 1). Perioperative prophylaxis showed protective effects on infectious complications (aHR 0.2 [0.09–0.46]), associated with lower infection prevalence (6.2 vs. 37.5%). In fact, 93.3% (387/415) received perioperative prophylaxis, in 91.5% of which Cefuroxime was applied with a median application time of 35 minutes before cut [IQR 25–45]. Conclusion: Among vascular surgery patients, procedure-related factors (open surgery and extended procedure time) contribute to the risk of VGI. In contrast, timely application of perioperative prophylaxis showed a highly protective effect on VGI development. Disclosures: All authors: No reported disclosures.